School Education — The Way Forward - Shukla, Ruchi (THE PRIMARY TEACHER, 2017)
This paper tries to ascertain if the Self-determination Theory and its concepts of competency, autonomy and relatedness, which lead to intrinsic motivation, can be utilised in solving the rising problem of stress among students, including those at the primary stage. Apart from theoretical interventions and approaches, one practical way of handling not just stress but related problems as well is by having trained teachers as ‘level one counsellors’. It is a teacher who serves as link among students, parents, school education system and administration. The presence of such a person in a school, whom students can reach out to, would not only ensure better stress management in them but also help build resilience and intrinsic motivation, enabling them become independent learners, who are self-driven and determined despite the challenges they face in life.